1992
DOI: 10.1007/bf03348657
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Raynaud’s phenomenon after L-thyroxine therapy in a patient with hypothyroidism

Abstract: A 50-year-old man is described who had a 15-year history of Raynaud's phenomenon with severe and frequent vasospastic attacks in his fingers and toes during the past years. Exacerbation of his digital symptoms, which started about 4 years ago, was accompanied by signs of thyroid deficiency, such as tiredness, memory impairment, decreased libido, constipation, dryness of skin and bradycardia. Hormonal evaluation revealed primary hypothyroidism and the patient began substitution therapy with L-thyroxine. After 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…These differences of TEWL in the summer may affect the deterioration of skin dryness in the winter. The skin blood flow functionality measured by CST may be involved in skin homeostasis during the 19,20 In addition to healthy subjects, an impaired RR is possibly involved in the dry skin symptoms of patients with these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences of TEWL in the summer may affect the deterioration of skin dryness in the winter. The skin blood flow functionality measured by CST may be involved in skin homeostasis during the 19,20 In addition to healthy subjects, an impaired RR is possibly involved in the dry skin symptoms of patients with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that no difference of the visual dryness score was observed between the high RR and the low RR groups in the summer, the TEWL was slightly higher in the low RR group (P < 0.1). 19,20 In addition to healthy subjects, an impaired RR is possibly involved in the dry skin symptoms of patients with these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of thyroid dysfunction in SSc may have an important impact also on the clinical manifestations of SSc; in fact, Raynaud's phenomenon is more difficult to control in hypothyroid individuals (44,45), and pulmonary hypertension (46) can be seriously influenced by hemodynamic changes of hypothyroidism. Thyroid function and ultrasonography should be tested as a part of the clinical profiling of SSc patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literatures reported that the pathophysiology of RP is complex and multifactorial, involving the endothelium, neuroreceptor expression, and locally produced mediators that affect vascular responses (2,3). Additionally, especially for the etiology of SRP, some different clinical disorders like hypothyroidism with high thyroid-stimulating hormone levels (4) or vascular toxicity associated with anti-neoplastic agents (5) or some rheumatic diseases like systemic lupus erythematosus, Sjogren's syndrome and scleroderma (2) were also considered re-sponsible for Raynaud's symptoms. Likewise, according to previous literature (6,7), Helicobacter Pylori (HP) can be a possible factor leading to RP.…”
Section: Introductionmentioning
confidence: 99%